Interfacial bonding and abrasive wear behaviours of the iron matrix composites - Li, Cong (2022)
Ceramic particles reinforced iron matrix composites attract considerable interest in the industrial engineering field due to the ceramic’s excellent fatigue and wear resistance. ZTA ceramic particle has been regarded as an ideal reinforcement phase. In this study, three-body abrasive wear behaviours and the mechanism of the ZTA/Fe composites and high chromium white cast iron Cr15 standard samples were investigated. The wear resistance of the ZTA/Fe composite was superior to the Cr15 standard sample under SiO2 abrasives. The extruded ZTA could protect the matrix surrounding ZTA ceramic particles. However, ZTA ceramic particles were cut together with the Cr15 matrix under SiC abrasives. The wear mechanism of the composites was a combination of the cutting and fatigue for SiC abrasives.